Ambiguity and Conflict in the Implementation of Policies for Determining Traditional Villages in Siak Regency - Rizan Hasbullah; Febri Yuliani; Hasim As'ari (Publica: Jurnal Pemikiran Administrasi Negara, 2022)
Traditional village is an original structure that has original rights in the form of rights including managing the territory and life of its customary law community. In order to realize the vision of Siak Regency to increase the existence of Malay culture in Siak Regency as the basis of identity in Siak society, and with the motto of Siak Regency "siak the truly of Malay", law no 6 of 2014 provides a potential and opportunity for the Government The Siak Regency area, to carry out rearrangement of the village by fixing it through the determination and formation of existing villages with the issuance of Regional Regulation No. 2 of 2015 concerning the determination of traditional villages in Siak Regency. The purpose of this research is to analyze the ambiguity and conflict in the implementation of the policy of establishing traditional villages in Siak Regency. This study used a qualitative research method with an exploratory approach. This study uses the Richard Matland Implementation model of Ambiguity and Implementation Conflict. This research was conducted in the traditional village of the Anak Swamp tribe, Sungai Apit District, Siak Regency, Riau Province. The results of this study when viewed from the four indicators of ambiguity and conflict by Richard Matland, only one has a high level of ambiguity and conflict, namely Experimental Ambiguity and Conflict. For this reason, it is hoped that the Siak district government can routinely evaluate process by process, so that it does not create high ambiguity and conflict between policy implementers and the community.